Six songs = Szesc piesni : with English and Polish words : 1. To the maiden grieving = Zasmuconej (Op 1)[bladmuziek] - Karlowicz, Mieczyslaw; Sliwinsky, Jan (Glasgow : The Polish Library Ksaznica Polska)
Bibliotheek Camille Huysmans
Engels
Pools
Partituur
Keywords: partituren